Rational Drugs Use Socialization in South Cicinde Village to Increase Health Promotion - Indah Laily Hilmi; Devi Ratnasari; Gun Gun Gumilar; Balqis Fitri Ayuni (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
People who have started to get used to using various types of drugs can cause errors in the use of drugs. Non-compliance with the rules of use in the use of drugs will result in problems such as drug side effects. Rational use of drugs is the selection and use of drugs whose effectiveness is guaranteed and safe, at the most favourable price. This activity aims to provide understanding, preventive health promotion, as well as information and studies to rural communities related to rational drug use. This activity was carried out in Cicinde Selatan Village with activity stages consisting of the preparation stage and the implementation stage. Data was collected before and after socialization using a survey questionnaire. Based on the data obtained, there was an increase in public knowledge after socialization regarding rational drug use from 11% to 90%